Tata Kelola Pemasangan Alat Peraga Kampanye Pemilihan Umum Serentak 2024 Ditinjau dari Hukum Lingkungan - Aliwafa, Muhammad (Forschungsforum Law Journal, 2025)
This research aims to analyze the supervision of the installation of campaign props (APK) which damage the environmental sustainability of the 2024 election campaign. Case studies in Central Bangka Regency show various violations of the installation of campaign props on trees, parks, electricity poles and bridge fences as well as through comparative studies of several regions. other. By using normative law (legal research) through statutory, case and comparative approaches. The results of the research resulted in a discussion of election regulations regarding the installation of campaign props as an effort to preserve the environment. Law Number 7 of 2017 concerning Elections with a comparative study of Law Number 32 of 2009 concerning Environmental Protection and Management. Through KPU and Bawaslu regulations as well as regional governments, an analysis of environmental sustainability regulations was then carried out to determine the impact of environmental pollution due to violations of APK installation. Violations in installing campaign props damage the environment in a number of areas. Incidents occurred in almost every region, the short campaign time was only 75 days and there were limitations and supervision by Bawaslu in a number of regions in following up on APK installation violations. Inherent and participatory supervision is needed to monitor APK installation violations that damage the environment. The regulatory urgency is for Bawaslu and its staff to be given access by local governments to supervise APK installation. Bawaslu's authority to supervise the installation of APKs needs to be given in the form of action to remove violating APK installations together with civil service police units. The recommendation of this research is that election participants, organizers and local governments create a collaborative script on the commitment to protect the environment in installing APK.